Work Experience, Placements and Internships - Steve Rook (UK Bloomsbury Academic, 2016)
This book provides students and graduates with a concise guide to work experience, placements and internships. It explores the full range of opportunities in key graduate sectors and offers support for each stage of the journey, from finding appropriate opportunities and applying for posts to developing a strategy and making the most of a placement. This is an indispensable resource for anyone applying for placements, internships and graduate jobs. It will also be a valuable resource for careers advisors and staff on employability, personal development and career planning modules.
Keywords: (ETB-2007) Travel and Tourism Work Placement